A nova lei de licitações como instrumento de aprimoramento da governança de aquisições nas universidades federais - Silva, Cristiane da (2024)
In 2021, Law no. 14,133/2021, known as the New Bidding Law, which brought changes and revoked all legislation previously in force, however, until 2023, public purchases could be carried out, based on the previous legislation or based on the new law. Considering that until 2023, according to criteria defined by the TCU. In this context, the general objective of this study was to analyze the potential of the new bidding law to improve procurement governance within Brazilian federal universities, from the perspective of employees who carry out activities inherent to contracting. To this end, this descriptive, documentary research with a predominantly qualitative approach collected quantitative data inherent to tenders based on the New Bidding and Contracts Law (NLLC), from the 69 universities, in 2023, on the National Public Procurement Portal – PNCP, as well as sent three different questionnaires to all 69 universities to be answered, respectively, by an auctioneer, a contracts manager and a contracts inspector. All 27 responding universities participated in the survey. The results showed that, in 2023, when universities could promote the opening of tenders governed by the old legislation or by the NLLC, among the 69 universities, 57 carried out tenders governed by the NLLC in 2023, and 12 of them did not carry out any tender governed by the new law in that year, when there was the possibility of promoting the opening of tenders based on the old legislation or based on the new legislation. In total, the UFs opened 1,411 bidding processes based on the new law, in which bids with estimated values and budget advertising predominated. Few universities used the power conferred by the new law to open bids with confidential estimated values. As for the modality, electronic auction was the most present modality, followed by electronic competition, and it is worth noting that Competitive Dialogues, a modality introduced by the new law, were not observed. Also considering the value of the budget registered in the PCA, only 27% of the aforementioned value was bid based on the aforementioned law, revealing that few universities were willing to bid in a preponderant way for the available budget based on the new law, in 2023. For the civil servants, the governance principle with the greatest focus in the new law was the improvement of hiring planning and the one with the least focus was responsiveness, however, in view of the responses from the research participants, the improvement was clear regulatory framework of the new law, for the governance of acquisitions within the scope of Public Administration.